The Influence of Equity Levels, and Liquidity on Profitability at PT Bank Sumut Pusat Medan City Period 2020 to 2022 - Silvia Putri Serum Perangin-Angin; Tridayana Br Sitepu; Aulia Darma Daulay; Bayu Wulandari (PT FORMOSA CENDEKIA GLOBAL, 2024)
A financial ratio analysis is critical for understanding a company's financial situation. Financial ratios play a vital part in determining How Many financial factors influence a company's future performance. This study was carried out to gather empirical data on the impact of equity and liquidity on profitability at PT Bank Sumut Pusat in Medan City. The data was gathered from monthly financial records evaluated at PT Bank Sumut Pusat in Medan City. Data was gathered through interviews and data management and then analyzed using multiple linear regression. In this study, the data was processed via SPSS. This study employed a sample of 36 monthly reports collected over three years. Specifically, the years 2020–2022. This study's findings demonstrate (1) Equity and liquidity do not have a concurrent and small impact on profitability, and (2) partial equity (3) Partial liquidity has no influence and is not substantial on profitability